Variables affecting the presence of mesenchymal stromal cells in peripheral blood and their relationship with apheresis products. (3rd February 2020) - Jain, Ankur; Khadwal, Alka; Sachdeva, Man Updesh Singh; Bose, Praveen; Lad, Deepesh; Bhattacharya, Shalmoli; Prakash, Gaurav; Malhotra, Pankaj; Varma, Neelam; Varma, Subhash
Summary: Mesenchymal stromal cells (MSCs) demonstrate the properties of self‐renewal, multipotentiality, and immunosuppression, which are responsible for their widespread clinical applications in tissue repair and regeneration. MSCs have been isolated from bone marrow, adipose tissue, and cord blood using culture in specialised media. Their presence in peripheral blood (PB) is debatable. We studied the presence of MSCs at baseline (PB) and following mobilisation with growth factors [PB and apheresis product (AP)] in patients undergoing autologous stem cell transplantation and healthy donors using flow cytometry. We conclude that both mobilised PB and AP are potential sources of MSCs. Given their small numbers in PB/AP, clinical use is feasible following ex‐vivo expansion. Variables affecting the presence of MSCs in PB and AP are also discussed.